Severe parental mental illness is associated with lower school readiness in offspring: A linked data study: IJPDS (2017) Issue 1, Vol 1:103, Proceedings of the IPDLN Conference (August 2016) - Bell, Megan; Bayliss, Donna; Glauert, Rebecca; Harrison, Amanda; Ohan, Jeneva (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Previous research has demonstrated an association between parental mental illness and adverse developmental outcomes in their offspring. If parental mental illness impacts on child development such that their offspring do not optimally develop the skills and abilities required for academic success, the effects may be long lasting. To date, the majority of research in this area has focused on maternal depression, with much less attention paid to other diagnostic groups or mental illness in fathers. It is important that we better understand the impact of parental mental illness on children’s development, so that the child’s needs may be incorporated into treatment alongside interventions for the parent. Data linkage provides us with a unique opportunity to conduct a comprehensive evaluation of this association. Approach Data from the Australian Early Development Census (AEDC) was used as a measure of early childhood development in five domains (physical health, social competence, emotional maturity, language and cognitive skills, and communication skills and general knowledge). Data were available for 22,890 Western Australian children aged 5-6 years, whose 2009 AEDC scores were linked to data on parental psychiatric hospitalisations. We identified parents with diagnoses of a range of mental illness diagnoses; parents who had more than one diagnosis; and mental illness in both mothers and fathers. Models were adjusted for child, parent and community socio-demographic characteristics. Results A total of 1069 mothers and 656 fathers had an inpatient psychiatric admission during the study period. The most prevalent diagnoses for both mothers and fathers were mood disorders, anxiety disorders, and substance abuse. Adjusted odds ratios with 95% confidence intervals were estimated for each AEDC domain using logistic regression. Parental mental illness was found to be associated with increased risk of offspring being developmentally vulnerable, compared to outcomes for children of parents without a psychiatric hospitalisation. This effect was equivalent for both parents, and was evident after controlling for socio-demographic factors. Conclusion These findings add support to recommendations that mental health professionals consider the impact of their patient’s psychiatric symptoms on the developing child when planning treatment. The study also shows that it is important to ensure that fathers are not overlooked in assessment and intervention. Family-based approaches to adult psychiatric care could meet the dual needs of intervention for parents and preventative measures for their offspring. These findings can inform policy regarding the importance of integrating and coordinating services to meet the needs of the family.